Postoperative Mobilization After Superior Rotator Cuff Repair: Sling Versus No Sling. (20th March 2019) - Tirefort, Jérôme; Schwitzguebel, Adrien J.; Collin, Philippe; Nowak, Alexandra; Plomb-Holmes, Chantal; Lädermann, Alexandre
Abstract : Background: Patients are commonly advised to wear a sling for 4 to 6 weeks after rotator cuff repair despite negative effects of early immobilization and benefits of motion rehabilitation. The aim of this study was to compare clinical and radiographic outcomes up to 6 months following rotator cuff repair with and without postoperative sling immobilization. Methods: We randomized 80 patients scheduled for arthroscopic repair of a small or medium superior rotator cuff tear into sling and no-sling groups (40 patients each). Passive mobilization was performed in both groups during the first 4 postoperative weeks, and this was followed by progressive active mobilization. Patients were evaluated clinically at 10 days and 1.5, 3, and 6 months and using ultrasound at 6 months. Univariable and multivariable analyses were performed to determine if postoperative scores were associated with sex, age at surgery, immobilization, arm dominance, a biceps procedure, resection of the distal part of the clavicle, or preoperative scores. Results: The sling and no-sling groups had similar preoperative patient characteristics, function, and adjuvant procedures. At 10 days, there was no difference in pain between the 2 groups (mean pain score [and standard deviation], 5.2 ± 2.3 versus 5.2 ± 1.9, p = 0.996). In comparison with the sling group, the no-sling group showed greater mean external rotation (23.5° ± 15.6° versus 15.3° ± 14.6°, p = 0.017) and active elevation (110.9° ± 31.9° versus 97.0° ± 25.0°, p = 0.038) at 1.5 months as well as better mean active elevation (139.0° ± 24.7° versus 125.8° ± 24.4°, p = 0.015) and internal rotation (T12 or above in 50% versus 28%, p = 0.011) at 3 months. Ultrasound evaluation revealed no significant differences at 6 months in tendon thickness anteriorly (p = 0.472) or posteriorly (p = 0.639), bursitis (p = 1.000), echogenicity (p = 0.422), or repair integrity (p = 0.902). Multivariable analyses confirmed that the mean American Shoulder and Elbow Surgeons (ASES) score increased with patient age (beta, 0.60; p = 0.009), the Single Assessment Numeric Evaluation (SANE) decreased with sling immobilization (beta, −6.33; p = 0.014), and pain increased with sling immobilization (beta, 0.77; p = 0.022). Conclusions: No immobilization after rotator cuff repair is associated with better early mobility and functional scores in comparison with sling immobilization. Postoperative immobilization with a sling may therefore not be required for patients treated for a small or medium tendon tear. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.